Temperatura e luz sobre tolerância ao frio na germinação, emergência e seletividade de herbicidas em arroz - Venske, Eduardo (2013)
Temperature and light have a complex interaction of plants, and may affect cold tolerance and herbicide selectivity. Two studies were conducted during the 2012 / 2013. In Article I the aim was to evaluate the relationship between temperature and light quantity and quality on the early development of rice cultivars and red rice biotypes. Two experiments were conducted, in the laboratory and in the greenhouse, during the months of July to November, 2012. The factors studied in experiment I were: temperature (25ºC and 18/13ºC); cultivar / biotype (IRGA 424 and PUITA INTA-CL / AV 6716 and AV 6722) and light (white, blue, green, yellow and red, shaders to 86 and 93% and dark). In the second experiment factors were season (August and November); cultivar / biotype (IRGA 424 and PUITA INTA-CL / AV 6716 and AV 6722) and light (white with coating, white, blue, green, yellow and red, shaders to 86 and 93%). The experimental design was in bands for temperature / time of sowing and light, and randomized to cultivar / biotype, with four replications. We evaluated normal seedlings, length of shoot and root, dry weight of shoots and roots and leaf area. Cultivars and biotypes studied have similar behavior against the light and temperature during early development. The light, especially red wave length, has increased tolerance to cold rice. In Article II the objective was to evaluate the effect of sowing date and artificially reducing the luminosity at different stages of plant development on the herbicide selectivity and yield components of rice. The field experiment was carried out in 2012/2013 harvest, and cultivar IRGA 424 was utilized. The factors studied were: sowing season (October 18 and November 09), herbicide (control - hand weeded, bispyribac sodium and penoxsulam) and stage of development of culture with luminosity reduced by 70% [control, seedling (S0-V4), vegetative, reproductive, and the entire cycle]. The experimental design was in bands for sowing date and reduced brightness, and randomized to herbicides, with four replications. Evaluated: plants, stems and panicles per area, herbicide injury, spikelets, filled and empty spikelets per panicle, spikelet sterility, thousand seed weight and yield. The sowing season influences the selectivity bispyribac sodium, and when held near the beginning of the period recommended reduces the productivity of farming. The artificial reduction of light in different phases of the cycle does not affect the selectivity of herbicides bispyribac sodium and penoxsulam on rice.